The medical student stressor questionnaire (MSSQ): validation and reliability in Turkish students - Funda Seher Özalp Ateş; Elif Akçay; Derya Gökmen; Süheyla Rahman (BMC Medical Education)
Abstract Background Medical training is a highly stressful environment for students. In previous studies, many instruments have been used to measure stress levels among medical students. However, these stress measurements are not specific tools for medical settings. This study aims to adapt the Medical Student Stressor Questionnaire (MSSQ) to Turkish, conduct validity and reliability studies, and provide a practical tool to evaluate medical school-related stressors of medical students in Turkey. Methods All students studying at the (Manisa Celal Bayar University) School of Medicine were invited to the study. The data was collected between January-March 2024. The research was completed with 412 students. The MSSQ consists of 40 items and 6 subscales. The psychometric properties of the MSSQ were evaluated through tests for validity and reliability. Using RStudio version 1.3.1093 (R Studio, PBC) with the lavaan package, confirmatory factor analysis (CFA) with the “diagonally weighted least squares (DWLS)” estimator was conducted. Internal consistency was tested by Cronbach’s alpha coefficient and test-retest reliability was examined by intraclass correlation coefficient (ICC). Results A total of 412 students participated in this study. The median (minimum–maximum) age of the students was found to be 20.00 (18.00–26.00) years. CFA was performed and the appropriate modification indices suggested by the model were added to the model. All 40 items loaded 0.38 or higher. The fit indices calculated as a result of the CFA were determined to be Root Mean Square Error of Approximation (RMSEA) = 0.060 (95% CI: 0.057–0.064)(p < 0.001), Comparative Fit Index (CFI) = 0.899 and Tucker-Lewis Index (TLI) = 0.888. The fit indices were at acceptable level. In the analyses conducted for the subscales, the Cronbach Alpha Coefficients were adequate. Conclusion In conclusion, this study has provided preliminary evidence for the validity and reliability of a Turkish version of the MSSQ. The six-factor structure was confirmed by CFA. We propose using the Turkish version of MSSQ to evaluate the stress level of medical students. Therefore, further research is needed to investigate the relationship between MSSQ and the other scales which used to measure stress.